2020
DOI: 10.3389/fmicb.2020.00249
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Hydrothermal Vent Biodiversity Toward Improved Biodiscovery Using a Novel in situ Enrichment Strategy

Abstract: Deep-sea hydrothermal vents are amongst the most extreme environments on Earth and represent interesting targets for marine bioprospecting and biodiscovery. The microbial communities in hydrothermal vents are often dominated by chemolithoautotrophs utilizing simple chemical compounds, though the full extent of their heterotrophic abilities is still being explored. In the bioprocessing industry, where degradation of complex organic materials often is a major challenge, new microbial solutions are heavily needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 69 publications
(86 reference statements)
0
22
0
Order By: Relevance
“…In addition, it is already well established that hydrothermally active and non-active areas of the AMOR host unique and poorly studied macrofauna, as well as a wide diversity of novel and uncultured microbial biodiversity (e.g., Dahle et al, 2015Dahle et al, , 2018Steen et al, 2016;Stokke et al, 2020). Metagenomic studies from the AMOR have identified novel archaeal lineages, which have challenged our views on the origin and evolution of eukaryotes and the topology of the tree of life (Spang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is already well established that hydrothermally active and non-active areas of the AMOR host unique and poorly studied macrofauna, as well as a wide diversity of novel and uncultured microbial biodiversity (e.g., Dahle et al, 2015Dahle et al, , 2018Steen et al, 2016;Stokke et al, 2020). Metagenomic studies from the AMOR have identified novel archaeal lineages, which have challenged our views on the origin and evolution of eukaryotes and the topology of the tree of life (Spang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomic studies from the AMOR have identified novel archaeal lineages, which have challenged our views on the origin and evolution of eukaryotes and the topology of the tree of life (Spang et al, 2015). In addition, recent in situ enrichment and culture of rare sedimentary microbes at AMOR vents have revealed great potential for biodiscovery of novel enzymes for use in biorefining and bioconversion of industrially relevant substrates such as those produced in fish farming and wood-pulping industries (Stokke et al, 2020). Given the high degree of novel findings during work in the area over the most recent years, it is likely that they represent only the tip of the iceberg when it comes to the amount of potentially valuable genetic resources present in the AMOR region.…”
Section: Discussionmentioning
confidence: 99%
“…Strains of the phylum Deferribacteres are the heterotrophic taxa commonly found in deep-sea vents that can grow with organic acids and proteinaceous compounds as energy sources, for example, Caldithrix abyssi (Miroshnichenko et al 2003b), Deferribacter abyssi (Miroshnichenko et al 2003a), D. autotrophicus (Slobodkina et al 2009a), D. desulfuricans (Takai et al 2003a, b, c). A high fraction of heterotrophic microbial lineages related to cultivated members within the order Thermotogales and Bacteroidetes, and many novel lineages were also enriched using a novel in situ enrichment strategy (Stokke et al 2020). Isolates in the phylum Deinococcus-Thermus have not only been isolated from hydrothermal vents but have often also been isolated from terrestrial hot springs.…”
Section: Heterotrophsmentioning
confidence: 99%
“…The biopolymer lignin significantly stimulates the growth of the Bathyarchaeota subgroup Bathy-8 (Yu et al 2018). By deploying in situ enrichment carriers in hot marine hydrothermal sediments, some thermophilic heterotrophic microorganisms that have not yet been cultured have been identified (Stokke et al 2020). Enrichment cultures of electrotrophic communities are obtained on electrodes and show a specific enrichment of Archaea belonging to the Thermococcales and Archaeoglobales orders in microbial electrolysis cells (specially designed bio-electrochemical system) under hyperthermophilic conditions (80 °C) (Pillot et al 2018).…”
Section: Perspectivesmentioning
confidence: 99%
“…The discovery of the hydrothermal vent ecosystem remains one of the biggest breakthroughs in our understanding of how life can be sustained in extreme conditions, marked by the first vent observation on the Galápagos Rift, in the eastern Pacific [ 3 ] and the discovery of the first black smoker vents [ 4 ]. Today, hydrothermal vents are well-known as attractive sites for bioprospecting of biotechnologically interesting enzymes [ 5 , 6 , 7 , 8 ] and other valuable biomolecules with potential industrial applications [ 6 , 9 , 10 ]. As with other marine biomes [ 11 , 12 , 13 ], hydrothermal vent environments are observed to be abundant with viruses, especially tailed dsDNA bacteriophages of order Caudovirales [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%